Kinaray-a Online, Isang Love Story Inang Wika bilang Instagram ng Alaala at Huling Museo / Kinaray-a Online, A Love Story : Mother Tongue as an Instragram of Curated Memories. - Asenjo, Genevieve L. (2015)
This is a preliminary valuation on the capacity and limitation of Mother Tongue, particularly of Kinaray-a, through the experience of Balay Sugidanun (House of Storytelling) as an online platform in the preservation and promotion of Mother Tongue via blogging, to dissemination in social media, for the possibility of forming new communities and alliances, in the time of Digital Humanities, Big Data, and Mother Tongue-based Multilingual Education (MTBLE) in the K to 12 program of the government.

The close reading is focused on the one-year blogposts of three leading guest bloggers based abroad. Working on the assumption that writing in Mother Tongue is a form of lyric arousal and an effective experience, here are the results: 1) Mother Tongue is a domestic image and metaphor of "land and sea in a plate" that became "play with words", 2) Mother Tongue is site and moment of things beautiful and good and sweet/delicious, and 3) Mother Tongue takes the shade of speia in the subject of remembering and worrying about. In the end, each blogpost functions as an Instagram of selected memory and Balay Sugidanun as a museum of curated memories in Kinaray-a.
Keywords: Mother tongue-based multilingual education (MTB-MLE)